Mothering Celebrities: Feminine/Feminist Agency and Subjectivity in the Auto/Biographies of an Indonesian Female Celebrity - Priyatna, Aquarini (Archīum Ateneo, 2024)
This article discusses motherhood and mothering as portrayed in two auto/biographies of Krisdayanti, a prominent Indonesian female celebrity. Written at two different times and contexts, the first one largely focuses on portraying Krisdayanti in her persona as an Indonesian glamorous celebrity at her peak as it is faithfully observed in her likewise glamorous auto/ biography. The other one, presented in a much simpler book design and more straightforward narration, depicts her more as an ordinary person in her varied roles as a celebrity, a wife, a mother, a daughter, and a sister. The article takes note of the important dynamics and complexity of Krisdayanti’s relationship with her mother and the significant roles that her mother plays that have shaped not only Krisdayanti’s personal life but also her career. The two auto/biographies have shown how feminist mothering foster the formation of feminine/feminist agency and subjectivity that are constantly and continuously shifting and traversing. More specifically, this article suggests that the auto/biographies have enabled a space to reveal the empowering experience of motherhood and mothering which have contributed to the construction of a particular form of femininity within celebrity culture.